Kualitas Layanan Klaim Asuransi yang Dibayarkan terhadap Kepuasan Nasabah Asuransi Allianz Syari'ah Jakarta (Area Tangerang) - Herlini Herlini; Eka Desiyanti; Maria Dewi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
Allianz Syari'ah (Allysa) Insurance is one of the insurance units within the Allianz insurance company whose primary business activity is to prosper the people, both individually and socially. Through the insurance products offered by Allysa, a customer is given the freedom to choose the type of insurance that suits his needs. However, often in providing the needs of its customers, some things must be considered, namely the quality of service and customer satisfaction. In this study, researchers tried to research the quality and customer satisfaction of Allianz Islamic insurance. Using the cluster sampling method and the Isacc table, the number of samples was only 32 respondents, then processed using several existing statistical tests.